1980
DOI: 10.1099/00221287-116-1-195
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Simple Fruiting Body-like Structures Associated with Sporulation under Aerobic Conditions in Clostridium acetobutylicum

Abstract: Isolated colonies of Clostridiurn acetobutylicun~, grown anaerobically for 2 d before exposure to aerobic conditions, developed into unique elongated fruiting body-like structures which reached a height of > 10 mm. The elongated structures were surrounded by an extracellular fibrous substance which formed a tough pliable sheath on exposure to air. Vegetative and sporulating cells were restricted to the basal region of the structure; the trunk region contained mainly free spores and a small number of granulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Colonies of C. acetobutylicum Δ perR further increased in diameter when conditions were shifted from anaerobic to aerobic, and hence were able to maintain growth in ambient air, but only after anaerobic pre‐incubation. Earlier studies on structure and morphology of colonies of C. acetobutylicum revealed that they are covered by a proteineacous sheath (Jones et al. , 1980) providing additional protection against the deleterious effects of oxygen and possibly creating a microoxic environment sufficient for continued growth of perR ‐deleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Colonies of C. acetobutylicum Δ perR further increased in diameter when conditions were shifted from anaerobic to aerobic, and hence were able to maintain growth in ambient air, but only after anaerobic pre‐incubation. Earlier studies on structure and morphology of colonies of C. acetobutylicum revealed that they are covered by a proteineacous sheath (Jones et al. , 1980) providing additional protection against the deleterious effects of oxygen and possibly creating a microoxic environment sufficient for continued growth of perR ‐deleted cells.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for employing multiple signalling systems may lie in the complex life cycle of these organisms, which not only involves a shift in fermentation metabolism, but also endospore formation and, under certain conditions, fruiting body formation [36]. These are all phenotypes for which quorum sensing control has been demonstrated in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, mathematical simulations of tumour growth show that under conditions of short oxygen supply, the morphology of the tumour is invasive, with small fingers or lobes protruding from the edge of the tumour body (Anderson et al 2006). This morphology of growth resembles that of colonies of anaerobic organisms, which produce typical flat spreading colonies with large spreading fans or lobes that grow out from the margins (Jones et al 1980).…”
Section: Hypoxia: the Optimal Environment For Cancer Cells And Lecamentioning
confidence: 99%